Validating the Nosocomial XDR Score: Novel Intervention of Improving Prescription Practices in the Era of Extensively Drug-resistant Pathogens in Hospitals. (4th October 2017) - Yekutiel, Matar; Lazarovitch, Tsilia; Zaidenstein, Ronit; Dadon, Mor; Daniel, Chen; Marchaim, Dror
Abstract: Background: In nosocomial sepsis, it is sometimes difficult to discriminate multi drug-resistant (MDR) infections (where empiric regimens usually suffice) from extensively drug-resistant (XDR) infections (where first-line empiric regimens commonly do not suffice). Delay in initiation of appropriate antimicrobial therapy (DAAT) is independently associated with worse outcomes among patients with XDR vs. MDR infections. A score that predicts XDR nosocomial infection could lead to reduced DAAT, improve outcomes, and contribute to antimicrobial stewardship efforts. In previous analyses, two scores (the "Vitkon score" and the "Michaeli score") were developed to differentiate MDR from XDR nosocomial sepsis. The study aim was to validate these scores on a general hospitalized population with nosocomial sepsis. Methods: A retrospective chart review based case–control analysis was conducted on adult patients hospitalized at Assaf Harofeh Medical Center (Israel), from which blood cultures were obtained due to suspected nosocomial sepsis, between 01/01/13–28/02/13. All patients were included regardless of their culture results. Validation of the XDR nosocomial sepsis scores were executed by using conventional methodologies and ROC curve analyses. Results: Overall, 406 patients with nosocomial sepsis were enrolled: 34 patients had XDR confirmed nosocomial sepsis (cases) and 372 had non-XDR nosocomial sepsis (controls). The "Vitkon score" had a sensitivity of 26%, and the ROC AUC of the "Michaeli score" was 0.55. In univariable analysis, patients with XDR sepsis had increased severity of acute illness indices ( P < 0.001), suffered from substantial DAAT ( P = 0.02), and had significant worse clinical outcomes, with longer hospital stays ( P = 0.005) and higher mortality ( P < 0.001). Conclusion: The study aim was to validate previously developed scores that differentiate MDR from XDR infection, on a cohort of patients with nosocomial sepsis. Yet, as reflected by this study, both scores' performances were inadequate. Larger prospective multicenter studies are needed, in order to develop and later-on validate such a score, which could improve the outcomes of patients with nosocomial XDR infections and contribute to stewardship efforts. Disclosures: All authors: No reported disclosures.